Literature Study of The Influence of Problem-Based Learning Model on Students' Mathematical Reasoning Ability - Nuryami (Kirana Publisher (KNPub), 2023)
This scientific work is a study of literature that discusses the effect of the Problem-Based Learning learning model on students' mathematical reasoning abilities based on various information such as books, journals, articles, and other scientific works. Five journals are used as a source of theory in this study, so the data or theory used is relatively straightforward and accurate. The method used in this scientific work is library research. The source of information was obtained from a study of 5 selected journals about the effect of Problem-Based Learning learning models on students' mathematical reasoning abilities. From this study, data was obtained that learning using the problem-based learning model positively influenced students' mathematical reasoning abilities. Therefore, using the PBL learning model can be a solution and strategy for solving problems found in life. The PBL model can be an innovative and varied solution in implementing classroom learning to improve students' mathematical reasoning and learning outcomes.